Evaluation of Social Media in Digital Supply Chain Management - Didik Madyatmadja, Evaristus; Nindito, Hendro; Pristinella, Debri; Tannady, Hendy (International Journal of Supply Chain Management, 2020)
In the past few years, many economies implement a social media-based digital supply chain management application for improving performance. However, there is problem regrading e-participation because of low level of participation by the public. The solution for improving public e-participation is by make a media for public do the e-participation, the media is social media-based digital supply chain management application. In fact, when a economy already implement the application, the participation is low. The purpose of this research is to identify factors that affecting behavior intention of public for do the e-participation using social media-based digital supply chain management application. In this research there are 203 social media-based digital supply chain management application users in Special Capital Region of Jakarta (Jakarta Aman application) that becoming research subject for evaluating the application for future development or references for other economy. The methodology approach for this study is based on combining many models such as Delon and McLean’s IS Success Model and TPB as the main model. Also combining external factors from existing studies that affecting attitude toward using the application. This paper can become references and contributing for making reader to understand more regrading people behavior for adopting social media-based digital supply chain management application to engage in e-participation. Social media can be an invaluable tool for supply chain professionals looking to identify new innovations, understand commodity and pricing trends, capture best practices, and collaborate with stakeholders, peers, and suppliers.